Haemophilus influenzae type b combination vaccines and atopic disorders: A prospective cohort study - I-Jen Wang; Li-Min Huang; Yueliang Leon Guo; Wu-Shiun Hsieh; Tien-Jen Lin; Pau-Chung Chen (Journal of the Formosan Medical Association, 2012)
Epidemiologic evidence for an association between vaccinations and atopy development is inconsistent. We evaluated the influence of Haemophilus influenzae type b (Hib) combination vaccines in 6-month-old infants on the prevalence of atopic disorders in 18-month-old children. Methods: We used multistage, stratified systematic sampling to recruit 24,200 mother–newborn pairs from the Taiwan national birth registration in 2005. Vaccination status was ascertained through official vaccine cards, while risk factors for atopic disorders were gathered by questionnaires at 6 months of age. Information about development of atopic dermatitis (AD) and recurrent wheezing was collected at 18 months of age. The relationship between atopic disorders and Hib combination vaccines, diphtheria–pertussis–tetanus–Hib and oral poliomyelitis vaccines (DPT-Hib&OPV) and DPT-Hib-inactivated poliomyelitis vaccines (DPT-Hib-IPV), were estimated by multiple logistic regression. Results: A total of 19,968 children completed the follow-up and participated in the study. AD was noted in 1584 (7.9%) infants while recurrent wheezing was found in 1220 (6.1%) infants. The adjusted odds ratios (ORs) (95% CI) for the development of AD in the DPT-Hib&OPV and DPT-Hib-IPV vaccination groups were given as 1.38 (1.15-1.65) and 1.49 (1.29-1.72), compared to those without Hib vaccination (DTP&OPV vaccination). However, the association between DPT-Hib&OPV and DPT-Hib-IPV vaccinations and recurrent wheezing failed to reach statistical significance. Conclusion: There is a potential risk for AD after receiving Hib combination vaccines. Hib vaccination is important to the public health, and therefore the observation requires further investigations.